PENGARUH PENDIDIKAN, PENGALAMAN KERJA DAN NON LABOR INCOME TERHADAP PENAWARAN TENAGA KERJA WANITA DI MAKASSAR - Rasyid, Rasdiah (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2016)
The purpose of this study was to determine and analyze the influence of education, work experience and non labor income on labor supply of women in the city of Makassar. kind of research is a verification of the test the answer to the problem. The data used in the form of quantitative data and qualitative data collected through interviews with married women workers who entered the labor market at micro and small enterprises in the city of Makassar. Data retrieval through research that takes a sample of the population and using questionnaires as a data collection instrument. This study uses non-probability sampling, in the form of Accidental sampling. The population in this study is a married woman who works at the micro and small enterprises in the city of Makassar. This study sample is numbered 55 respondents. Data analysis techniques used in the study were multiple linear regression. The conclusion of this study is the education, work experience and non labor income and a significant positive effect on labor supply of women in the city of Makassar.